2018 AHA/ACC Guideline for the Management of Adults With Congenital Heart Disease: Executive Summary. Issue 14 (2nd April 2019) - Stout, Karen K.; Daniels, Curt J.; Aboulhosn, Jamil A.; Bozkurt, Biykem; Broberg, Craig S.; Colman, Jack M.; Crumb, Stephen R.; Dearani, Joseph A.; Fuller, Stephanie; Gurvitz, Michelle; Khairy, Paul; Landzberg, Michael J.; et al.
Abstract : Supplemental Digital Content is available in the text.